Promoting Health and Wellbeing of migrants in Europe: “transformative” pedagogical and didactical perspectives. The case of the Erasmus+ Project “APELE. Accreditation of Prior Experiential Learning Experiences” - Gallelli, Rosa; Renna, Pasquale (Pensa MultiMedia, 2021)
European Union recognizes the need of migrants for a dignified life, in which they can exercise the fundamental right to education and work. For this reason, among the pedagogical and didactic tools aimed at reconstructing professional biographies often fragmented and made untraceable by the devastation of wars and famines, the European Union recognizes and promotes, today, the portfolio of skills as a tool for recognizing qualifications. and professional qualifications. In this context, the University of Bari has fielded significant pilot experiences. In this case a research project will be presented, still in progress, in which University of Bari is involved together with the Universities of Akureyri (Iceland), Copenhagen (Denmark) and Patras (Greece). It is called “APELE - Accreditation of Experiential Learning Experiences”. Through this Project we intend to answer important research questions including: How do the processes of continuous training change over the time of Mediterranean migrations? How does school and professional training change for migrants who arrive in Italy without the possibility of demonstrating their previous school and work training? How does citizenship education change in a logic of proximity to migrants, with their fundamental rights to education and health? How to train in intercultural dialogue and planetary citizenship in the European Union, involved by an epochal migration of peoples? Il presente contributo si propone di tratteggiare, nelle sue linee fondamentali, la valenza pedagogica del Portfolio delle competenze in quanto strumento di promozione della dignità e del benessere individuale e sociale dei migranti in Europa e, nella fattispecie della presente trattazione, in Italia. Sarà presentato, in tale contesto, un Progetto di ricerca, tutt’ora in fase di svolgimento, in cui è coinvolta l’Università di Bari assieme alle Università di Akureyri (Islanda), Copenhagen (Danimarca) e Patrasso (Grecia), dal titolo “APELE – Accreditation of Experiential Learning Experiences”. ...